Renewal Paradigm of the LDII Community in Kediri - Muhammadiyah, Hilmi (Al-Albab, 2019)
This article attempts to explore the dynamics of the Lembaga Dakwah Islam Indonesia (LDII) or Indonesian Islamic Da'wah Institution community in Kediri of East Java, Indonesia in maintaining its existence, transforming and seeing the processes, patterns, and strategies that developed by the LDII. The article elaborates how social actors of the LDII carry out social practices continuously so that LDII can continue to survive, develop, and reform the doctrine and religious identity paradigm and its organizational identity thus being accepted by people in the region. The role of the actors as the agent in changing the character of the movement is discussed in this work. They have made strategies including building closeness to the authorities, building attitudes of openness, changing the image of the organization, strengthening identity, establishing dialogue and public cooperation with the Indonesian Ulema Council (MUI – Majelis Ulama Indonesia) that positioning LDII as a heretical and splinter organization, and establishing cooperation with Religious Community Organizations (Ormas) that are considered mainstream, such as NU (Nahdatul Ulama) and Muhammadiyah. This work attempts to provide materials and considerations in dealing with the issue of raising between the flow of splinters and established groups.